An efficient synthesis, characterization and docking studies of 2‐methoxy‐3‐(1‐substituted‐1H‐pyrazol‐3‐yl)quinoxalines. Issue 2 (24th April 2021) - Rachala, Muralidhar Reddy; Eppakayala, Laxminarayana; Tharikoppula, Giri; Maringanti, Thirumala Chary
Abstract: A basic, proficient and P‐TSA catalyzed synthesis of quinoxalines beginning from ethyl 3‐methoxyquinoxaline‐2‐carboxylate in great yields is introduced. All the compounds synthesized were analyzed by spectral analysis.